Leishmania y su influencia en úlceras cutáneas en habitantes de la ciudadela barrio chino cantón Montalvo Los Ríos primer semestre 2015 - Ochoa Macias, Ingrid Katherine (2015)
Leishmaniasis is caused by a protozoan parasite of the genus Leishmania, transmitted by the bite of infected sandflies. There are three main forms of leishmaniasis: visceral (the way more grave illness, often an area known as kala-azar), cutaneous (most common) and mucocutaneous. The disease, which affects the world's poorest populations, is associated with malnutrition, population displacement, poor housing conditions, a weak immune system and lack of resources. That is why in the present study was to determine the prevalence of Leishmaniasis and its influence on skin ulcers Inhabitants of the citadel Chinatown Canton Montalvo province of Los Rios in the first half of 2015. The methods used para esta Were Experimental Research - Laboratory and el inductive method. The type of study conducted in the Research Laboratory WAS because by the same S. was able to determine the incidence of leishmaniasis in Barrio citadel cross cutting chino.Y as I was done with a household survey in this citadel With A stratified sampling by location. To determine the incidence of Leishmaniasis S. Were evaluated 112 inhabitants of the citadel Chinatown, once made the analysis of samples obtained S. could be determined that 4.5% of samples were positive. The population was classified by age and sex, where if sex could be determined S. That most affected is the male with 80.0% of positive cases and the predominant age group is that of 41-50 years 60.0 % of cases, a difference group 51-62 years 40.0% of cases, this probably what Persons in this age range are more productive and therefore the most exposed.